D'Oriental Auto Trading / Mohd Zakir Tahir... [et al.] - Tahir, Mohd Zaki; Mohd Khir, Munauwir; Mohd Shariff, Ahmad Hisham; Yusak, Zulkiflee; Halim, Mohd Shahrul Nizal; Abd Kadir, Khairil Amri (2000)
D'Oriental Auto Trading is a firm set up by its 6 members as a partnership firm where they will particularly run a business on distribution of imported cars. The main activity was distributing and selling of imported cars. The business was started on January 2000 and it was located at Bandar Wangsa Maju, Kuala Lumpur.